PERSEPSI DAN TINGKAT KEPUASAN PETANI TERHADAP KUALITAS BENIH PADI DI LAHAN FOOD ESTATE PROVINSI KALIMANTAN TENGAH - Feronika, Evi; Taufik, Eko Nor; Margaretha , Dona Brenda (University of Islam Malang, 2024)
This study aims to (1) analyze farmers' perceptions of the quality of rice seed assistance in Central Kalimantan food estates. (2) Analyze the level of farmer satisfaction with the quality of rice seed assistance in Central Kalimantan food estates. This research was conducted on farmer groups who obtained new superior variety seeds (VUB) in Belanti Siam Village, Pandih Batu District, Pulang Pisau Regency. Deliberate choice of location (Purposive). The sampling in this study was carried out using the Slovin formula, because there were 12 farmer groups in the population in this study, several samples were taken from each farmer group according to the number of farmers in each group with an error rate of 10%. namely as many as 84 farmers. The method used to answer the first objective is descriptive method through interviews and using a Likert Scale. Then the method used to answer the second objective is the Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) methods. The results showed that farmers' perceptions of the quality of the rice seed assistance showed a score of 6,835 with an index of 67,80% and belonged to the good category. The level of farmer satisfaction with the quality of rice seed assistance from several different attributes. Based on the results of the analysis using the CSI method, farmer satisfaction with the rice seed assistance has an index value of 64.04%. The farmers who received the rice seed assistance in Belanti Siam Village were quite satisfied with the quality of the seeds they obtained.